Implementation of Character Education in Private Elementary School in Cimahi City - Anjar Maulana Nuraziz; Veny Juniarni Hardi; Sumbara Hambali (Journal of Physical and Outdoor Education, 2026)
This study aims to explore the experiences of Physical Education, Sports, and Health (PJOK) teachers in implementing character education at private elementary schools in Cimahi City. Character education has become a central issue in education due to the moral decline among the younger generation. PJOK teachers play a strategic role in shaping students' character through physical activities that emphasize values such as discipline, sportsmanship, cooperation, and responsibility. This research employs a qualitative approach with a phenomenological method. Data were collected through in-depth interviews with two experienced PJOK teachers from private elementary schools in Cimahi. Data analysis was conducted thematically based on Miles and Huberman's framework, including data reduction, data display, and conclusion drawing. The findings reveal that PJOK teachers integrate character values through modeling, group games, reflective discussions, and positive reinforcement. The main obstacles encountered include limited instructional time, lack of facilities, and students' low awareness of character values. In conclusion, PJOK learning plays a crucial role in holistic character development, and teachers' experiences can serve as valuable insights for prospective educators to implement effective character education in elementary schools.